The Myths of Heaven-Sent Creativity: Toward a Perhaps Less Democratic But More Down-to-Earth Understanding. Issue 3 (2nd July 2016) - Cropley, Arthur
Abstract : Creativity is surrounded by a cluster of long-held beliefs—referred to here as myths —which regard it as confined to aesthetic/spiritual domains and as a divine gift to a tiny few, and thus render it ineluctable, ineffable and inscrutable. As a result, treating it as part of normal psychological functioning and emphasizing its usefulness seems almost blasphemous, and is regarded by some as devaluing creative talent or even rendering the idea of creativity meaningless. Indeed, there really does seem to be a danger of commodifying creativity and reducing it to fast food creativity —attractively packaged but lacking genuine nutritional value. However, a phase model of the process of creativity makes it possible to distinguish between sublime creativity, mundane creativity, and commodified creativity without attributing the former to forces beyond mere human existence. This conceptualization has practical consequences for, for instance, education.